Differences in Knowledge of Teenage Girl Before and After Being Given Health Education by Using Animated Video About Human Papillomavirus Vaccinatoin - Ni Luh Kade Manik Wulandari; Ni Nyoman Suindri; Listina Ade Widya Ningtyas (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Cervical cancer is the second deadly disease that occurs in women. The prevalence of cervical cancer in Indonesia in 2021 is 36,633 cases or 17.2% of all cancer cases in women. Cervical cancer has a high mortality of 19.1% of all cancer deaths. Human Papillomavirus (HPV) is the main factor causing cervical cancer. The purpose of this study was to determine the differences in knowledge of teenage girl before and after being given health education by using animated video about HPV vaccinatoin. This pre eksperimental research used one group pretest posttest design which conducted in April 2024 with proportional cluster random sampling. Sampel used 56 teenage girl VII grade students of SMP Negeri 2 Kediri. Data collected by questionnaire. Data analysis used inivariate with frequency distribution and bivariate with Wilcoxon test based on significance level p<0,05. The results of the different hypothesis test found that the value of p= 0,000, so it could be concluded that there were the differences in knowledge of teenage girl before and after being given health education by using animated video about HPV vaccinatoin. It is suggested that further research to develop this study with other variables related to cervical cancer prevention with HPV vaccination.